Picturing the Boundary Between Good and Bad: The Lighting, Framing, and Camera Movement of “Kidnap” - Christa Azalia Tedjorahardjo (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
This creative work is a cinematography report from the screenplay “Kidnap” by Indah Sari Y. The story tells about a criminal who is given a mission to kidnap the daughter of a deceased wealthy CEO, however the Man realized that he mistakenly kidnapped the wrong person. He is caught in the dilemma whether or not to let her go, yet his situation only gets worse when he is given the order to kill her. The cinematography of this film aims to convey the story and message that the director envisioned. Moreover, it aims to portray characterization through various elements of cinematography such as framing, lighting, and camera movement. It also intents to manipulate tone and mood through those cinematographic elements. To further understand the cinematography of this film, three main theories are used: low-key lighting, head-room and lead-room, and handheld camera movement. These theories are to help the cinematographer to convey the genre of psychological suspense, with the subgenre of crime drama. An in-depth analysis in this report will talk in details about how cinematography achieved the desired effects towards characterization, mood, and tone.